Characterization and flexural strength of iceberg and glacier Ice - Gagnon, R. E.; Gammon, P. H. (1995)
Flexural strength of iceberg and glacier ice was determined from four-point beam-bending experiments. A large quantity of glacial ice was collected from four icebergs and one glacier, and a detailed ice-characterization program was performed on samples from the five sources. Beam-bending experiments were conducted at 4 temperatures in the range -1° or -16°C and at strain rates of 10 (-3) and 10(-5) s(-1). The flexural strength was found to increase with and increasing strain rate (based on extreme fibre strain) and decreasing temperature. The data suggest that air-bubble inclusions play an important role in determining the flexural strength of glacial ice and this can explain the significant differences in mean strenght of the ice from the five sources. At a strin rate of 10(-3) s(-1) and temperature of -11°C, the flexural strength was found to increase as the number of bibbles per unit colume increased. Reduction of crack-initiating stresses at grain boundaries by "softening" of grains due to intragranular air-bubble inclusions is thought to be the mechanism. Peer reviewed: Yes NRC publication: Yes